A implementação das novas tecnologias da informação e suas implicações nos processos de trabalho dos bibliotecários: um estudo de caso no Núcleo Integrado de Bibliotecas da UFMA NIB/UFMA - Costa, Maria de Fátima Oliveira (2015)
Case study on the Central Library (BC) of Libraries Integrated Nucleus from the Federal University of Maranhão (UFMA/NIB) with the purpose of analyzing the transformation that have occurred in the work of the librarians in face of the implementation of the new information technology SIG- Modules SIPAC and SIGAA in BC of NIB/UFMA. The chosen population for the development of the research was concentrated in 12 (twelve) librarians that develop their activities in the sectors: control service and formation of collection (SCFA), technical processes service (SPT), and bibliographical information service (SIB). The data were collected through interviews and documentary research that subsidized the analysis of the results. The theoretical framework of the study talked about the information technology and its implications on the work processes of the enterprises and libraries; the evolution of the libraries and university libraries and; the work processes in the context of the world of work, work in libraries and the relationship with the information technology. The analysis of the data showed that the work processes of the BC librarians have become as a result of the implementation of this new technology, bringing consequences in the forms of execution of the tasks, leading them to adapt and create new ways for the development of their activities, in order to correspond to the demands generated. Detach that the introduction of the new technologies allowed to the librarians and the manager of the library a greater control over the work and caused even greater accessibility and visibility of library services to the academic community. Propose actions for adequacy of the work processes of the librarians, that converge with the new technologies. It is concluded that the use of the new information technology SIG- Modules SIGAA and SIPAC by NIBUFMA, brought transformation in the work processes of the librarians, affecting the daily practices, mainly because these professionals were already trained and accustomed to acting with the previous technology that used some manual routines combined with mechanical technologies.